2017
DOI: 10.1111/jcpt.12652
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dexmedetomidine administered to patients with end-stage renal failure and secondary hyperparathyroidism undergoing general anaesthesia

Abstract: The pharmacokinetics of dexmedetomidine were best described by a two-compartment model in our study. The pharmacokinetic parameters of dexmedetomidine in patients with end-stage renal failure and hyperparathyroidism were similar to those in patients with normal renal function. Further studies of dexmedetomidine pharmacokinetics are recommended to optimize its clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is metabolised by glucuronidation and CYP2A6 hydroxylation and subsequently excreted in urine almost exclusively as metabolite [2]. Its pharmacokinetics has been described by a two-compartmental model both in adults [3][4][5][6][7] and children [8][9][10][11][12]. Still, other investigators have also reported the disposition of dexmedetomidine according to one-compartment [13] and three-compartment [14][15][16] models.…”
Section: Introductionmentioning
confidence: 99%
“…It is metabolised by glucuronidation and CYP2A6 hydroxylation and subsequently excreted in urine almost exclusively as metabolite [2]. Its pharmacokinetics has been described by a two-compartmental model both in adults [3][4][5][6][7] and children [8][9][10][11][12]. Still, other investigators have also reported the disposition of dexmedetomidine according to one-compartment [13] and three-compartment [14][15][16] models.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of α-2 agonists specifically in RSS has been reported, but only in case reports so far ( 36 , 37 ). We chose dexmedetomidine over clonidine because it has many advantages: it is approved for sedation of critically ill patients, and has a short half-life without alteration in patients with impaired renal function ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…DEX was administered to maintain sedation during the operation because its pharmacokinetic parameters in patients with end-stage renal failure are similar to those in patients with normal renal function. 30 More importantly, it has no adverse effect on kidney function. We used tramadol as rescue analgesia for postoperative analgesia insufficiency because nonsteroidal drugs are inappropriate for these patients, and potent opioids are not necessary because of the small incision.…”
Section: Discussionmentioning
confidence: 99%